Investigation on mechanical behaviour of dacite under loading and unloading conditions. Issue 2 (15th April 2019) - Wang, S.; Wang, H; Xu, W; Qian, W.
Abstract : Dacite is the dam site material of Rumei Hydropower Station, Tibet, China. To study the deformation and failure mechanisms of dacite under loading and unloading conditions, a series of triaxial compression tests and unloading confining pressure tests were carried out. Experimental results indicate that the deformation and strength behaviour of dacite are different between loading and unloading conditions. The lateral strain is more sensitive to the decreasing of the confining pressure under unloading process. In a uniaxial compression test, the sample is axial splitting. Shear failure takes place under the confining pressure. However, the samples failed with combined shear and tensile fractures in unloading confining pressure tests. From the viewpoint of energy conversion, the failure of dacite in triaxial compression process is determined by the released elastic strain energy, while the dissipated strain energy plays a major role in unloading confining pressure process.